Exploring the Role of Social Psychological Drivers in Small Scale Textile Business Environment of Northern Province of Sri Lanka - Lochani, M.M.M.; Kumarasinghe, J.A.D.P.M.; Ranasinghe, R.A.G.N.; Kumara, M.G.R.D.; Kumarasinghe, M.M.S.L.; Rajapaksha, R.M.K.D.; Kodithuwakku, K.K.T.D.; Wickramasekara, D.H.T.; Bandara, M.D.D.; Rajapaksha, R.M.O.; Dilogini, S. (Faculty of Management Studies | Rajarata University of Sri Lanka, 2025)
Despite the significant presence of small-scale textile businesses in Northern Sri Lanka, little is known about how social and psychological factors influence consumer behaviour in this context. Understanding these drivers is critical for improving business performance, customer loyalty and community engagement. This study aims to explore how social psychological factors such as identity expression, peer influence and emotional attachment affect consumer behaviour and the success of small-scale textile businesses, providing actionable insights for local business management and community development. A qualitative approach was adopted to capture in-depth perspectives from both consumers and business owners, gaining a deeper understanding of how social and psychological factors shape their buying decisions. Researchers collected data through two semi-structured interviews with the owner and employee and six focus group discussions with consumers (three with regular customers and three with non-regular customers) of a small-scale textile in Northern Sri Lanka. These participants were selected through purposive sampling. Interviews with the owner and employee revealed that business practices emphasizing personal relationships, consistent product quality and community engagement are central to building brand trust. Focus group discussions with consumers highlighted the importance of affordability, fashion trends, peer influence, and emotional attachment to supporting local businesses. The study highlights the importance of local values, trust and customer loyalty for the success of small-scale textile businesses. Practical implications include improved management practices, customer engagement strategies, and fostering group identity among loyal customers. Socially, the findings promote the empowerment of local communities, strong trust-based consumer-producer relationships, inclusion and building authenticity. This research presents a novel application of social psychology to the textile industry.
Keywords: Local values; Qualitative approach; Small-scale business environment; Social psychological factors; Thematic analysis